The Release of Fertilizer on Corncob Cellulose – Based Acid-Acrylamide Hydrogel Prepared by Chemical Cross-Binding Method - Renda Amalia Anggraini; Mersi Kurniati; Christina Winarti; Irmansyah Irmansyah (Dept. of Chemical Engineering, Diponegoro University, 2021)
Farmers' knowledge of the amount and dosage of fertilizers recommended for a practical fertilization system is low. As the result, the plant does not fully absorb the given fertilizer. Some fertilizers are leached by the flowing water and wasted into the soil layer. In long term basis, this practice can cause environmental pollution, especially on the land, water and air. Due to this fertilization problem in agriculture practice, a material with a high-water absorption capacity, which further releases it together with the fertilizer over a desirable period of time, is needed. One way to effectively provide water and nutrients to the plants and improve the physical and chemical properties of the fertilizzer is by the application of hydrogel. In this work, the release of urea fertilizer in a hydrogel-based on corncob cellulose was prepared using N, N'-Methylene Bis-acrylamide (MBA) as a crosslinker was studied. This research aims to produce a hydrogel with good physical and mechanical properties using acrylamide based on corn cobs cellulose and can be applied as a fertilizer carrier matrix whose structure can regulate fertilizer release. The treatments tested were MBA concentrations of 0%, 1%, and 2%, while the ratio of cellulose: solvent was 1: 2 and the addition of urea fertilizer with a concentration of 5%. The results showed that the swelling value increased with increasing acrylamide in the treatment ratio of the concentration of cellulose: acrylamide-acrylamide (NS: AAm). Fertilizer factors also gave a good swelling value. This shows that the addition of fertilizers gives maximum results. The hydrogel with the best treatment, namely the concentration ratio of 1% MBA, produced a swelling value of 7633.3%, a gel fraction of 76.51%, 1.73 miligram fertilizer loading, fertilizer release by 2.9%, a hardness of 7,865 N, with the morphology showing urea crystals in the form of white spots and showing the results of a slow but optimum release rate of fertilizer so that it can be applied for agriculture that requires a lot of nutrients at the beginning of growth.Keywords: corncorb; cellulose; hydrogel; N’,N’-Methylene Bis-acrylamide (MBA), slow released fertilizer